PROFIL BERPIKIR KRITIS SISWA KELAS VII-A SMP NEGERI 1 JEMBER DALAM MENYELESAIKAN SOAL ARITMETIKA SOSIAL - Sugiarti, Titik; Suryanti, Putri Dwi; Susanto, Susanto (Department of Mathematics Education , University of Jember, 2017)
Abstract. This study aims to describe the critical thinking ability of students of class VII-A SMP Negeri 1 Jember in solving the problem of social arithmetic. The type of this research is descriptive research with qualitative approach. Data collection methods used were tests and interviews. The subjects of the study were students of class VII A SMP Negeri 1 Jember which amounted to 36 students. Thinking ability of students can be seen from the ability to analyze the information contained in the question, the ability to analyze the intended purpose in question, able to provide assumptions or opinions about the problem, able to determine the solution contained in the problem, able to develop other reasonable ways of completion, able to write down the answers or solutions of the problems, able to determine the conclusions of the solution problems that have been obtained. The results show that students are able to analyze the problem well and can meet 6 of the 7 indicators of critical thinking. One unfulfilled indicator is the ability to find alternative ways to find solutions of the problems. From the answers obtained from students can be concluded that the students of class VII-A are able to think critically well by analyzing the information contained in the question, although not yet can use alternative other ways of completion. Keywords: Social Arithmetic,Critical Thinking, Critical Thinking Skills, Problem Solving.